Design analysis and fabricate a functional grabber for robotic arm car - Tengku Mohd Faiz, Tengku Muhammad Adam (2024)
A grabber for a robotic arm car is a well-known machine that has been deployed and used globally. It offers a lot of benefits in this day and age. First, the grabber is used to pick up an object of various shapes. There are many grabbers that already exist in this modern day, but they are not specifically for use in the kindergarten environment. In order to create the grabber for a robotic arm car to put it in kindergarten, it has to improve the design that already exists. The objective is to design and fabricate a functional grabber mechanism for a robotic arm car that is capable of securely grasping. This project shows the details of the process to produce the machine, from its design to fabricating it and all the manufacturing processes that it will undergo. This project aims for kindergarten teachers to help caretakers do chores while being more relaxed and to expose kids and children to the robotic world, thus making them interested and excited to know more and learn more about robotics.